Devic's disease before Devic: bilateral optic neuritis and simultaneous myelitis in a young woman (1874) - Jarius, Sven; Wildemann, Brigitte (Journal of the neurological sciences, 2015)
Neuromyelitis optica (NMO, Devic's disease) is an often severely disabling disorder of the central nervous system (CNS) which mainly affects the optic nerves and spinal cord. NMO was long considered a clinical subform of multiple sclerosis (MS). In 2004, however, Lennon and colleagues described a novel autoantibody in NMO which targets aquaporin-4, the most abundant water channel in the CNS, and which was later shown to be directly pathogenic. This has led to the recognition of NMO as a distinct disease entity in its own right. While the history of ‘classical’ MS has been extensively studied, only little is known about the early history of NMO. The term neuromyelitis optica was coined in 1894 by Eugène Devic (1858-1930) and Fernand Gault (1873-1936), who were the first to provide a systematic description of that disorder. Here we re-present a very early description of a case of NMO by a Polish physician, Adolf Wurst, which appeared in 1876 in Przegląd Lekarski, one of the oldest Polish medical journals. This report predates Devic and Gault's seminal work on NMO by more than two decades. The patient, a 30-year-old woman, subacutely developed simultaneous bilateral optic neuritis with papilloedema and bilateral blindness and transverse myelitis with severe paraparesis, anaesthesia, and bladder and bowel dysfunction. At last follow-up, one year after onset, she had recovered except for a residual spastic gait and some visual deficit on the right side. Of note, this is the first known case of NMO in a Caucasian patient ever reported outside Western Europe.
Gesehen am 19.06.2020